Historical blocking: CN 2019-06-03 to 2019-06-05 (China) - Voidly (Voidly Global Censorship Index, 2019)
CRITICAL severity censorship detected in China. Data sourced from ooni-historical-backfill.
Censorship Incident ID: CN-2019-0006. Severity: critical. Confidence: 80%